Malestar psicológico en estudiantes universitarios: una mirada desde el modelo de promoción de la salud - Mosqueda-Díaz, Angélica (Universidad de Sonora, 2019)
This article has as purpose to ana - lyze the psychological discomfort phenomenon conceptually, recognize the magnitude of this problem on college students and analyze this phenomenon from the Model of Health Promotion. Psycholog - ical discomfort is a mental health problem, although not a psychiatric disease produces a series of clini - cal expressions that alter the nor - mal performance of people, so its main features and expressions are analyzed. College students are par - ticularly vulnerable to develop this problematic group, so personal and contextual characteristics that ex - pose them to a series of stress fac - tors associated with college expe - rience are presented, which causes more than 40% manifest symptoms that can attributed to psychological discomfort. The magnitude of this situation requires that the disciplines of thearea of health provide alter - natives to address this phenomenon. From the Nursing Theory “Model Health Promotion” posed by Nola J. Pender, seems to offer interesting to address these conceptual aspects, so a proposal is presented to analyze the psychological discomfort among college students from this theoretical position.